Hepatitis C virus incidence in HIV‐infected and in preexposure prophylaxis (PrEP)‐using men having sex with men. (10th August 2018) - Cotte, Laurent; Cua, Eric; Reynes, Jacques; Raffi, François; Rey, David; Delobel, Pierre; Gagneux‐Brunon, Amandine; Jacomet, Christine; Palich, Romain; Laroche, Hélène; Cabie, André; Hoen, Bruno; et al.
Abstract: Background & Aims: HCV incidence still appears on the rise in HIV‐infected MSM in France. We assessed the incidence of HCV infection in HIV‐positive and in preexposure prophylaxis (PrEP)‐using MSM. Methods: HIV‐infected, HCV‐negative MSM with serological follow‐up in 2016 and HIV‐negative, HCV‐negative PrEP‐using MSM enrolled from January 2016 to May 2017 in the French Dat'AIDS cohort were analysed to assess the incidence of a primary HCV infection. The incidence of HCV reinfection was also determined in patients having cured a previous infection. Results: Among 10 049 HIV‐infected MSM followed in 2016, 681 patients were already HCV‐infected when entering the study (prevalence 6.8%). Serological follow‐up was available in 2016 for 4151 HCV‐negative patients. Virological follow‐up was available for 478 patients who had cured a previous infection. Fifty‐seven HCV infections occurred in 2016 (42 primary infections, 15 reinfections). Incidence of primary HCV infection, reinfection and overall HCV infection was, respectively, 1.0, 3.1 and 1.2/100 person‐years (PY). From January 2016 to May 2017, 930 HIV‐negative subjects were enrolled for PrEP. Seventeen patients were already HCV‐infected (prevalence 1.8%). Twelve HCV infections occurred during follow‐up (10 primary infections, 2 reinfections) giving an incidence of primary infection of 1.0/100 PY and an overall incidence of 1.2/100 PY. Conclusions: The overall incidence of HCV infection and of a primary HCV infection in HIV‐positive and in PrEP‐using MSM appeared similar in France in 2016 to early 2017. HIV‐positive and PrEP‐using MSM probably share similar at‐risk practices and both should be targeted for preventative interventions. Abstract : See Article on Page1733